Tax Avoidance: Capital Intensity, Profitabilitas, dan Leverage pada Perusahaan Pertanian di BEI Tahun 2016-2021 (Institut Agama Islam Negeri Kudus, 2023)
This study aims to determine whether or not there is an influence between capital intensity, profitability, and leverage on tax avoidance in agricultural sector companies listed on the IDX in 2016-2021, using associative research types and quantitative approaches. Therefore, the data used is secondary data sourced from the official website of the Indonesia Stock Exchange (IDX). The samples used in this study were 7 companies with the sampling technique using purposive sampling method. The results of the research were analyzed using the Eviews 12 Student Version showing that capital intensity has a positive effect on tax avoidance, profitability has no effect on taxes, and leverage has a positive effect on tax avoidance.Keywords: Capital Intensity, Profitability, Leverage, Tax Avoidance